PRELIMINARY DATA FOR THE SHARR MOUNTAIN FLORA - MACEDONIA - Abdii, Nasuf (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
In this paper are presented partial data of a two year work (March 2013 - November 2014) on DATA ON FLORA, HABITAT AND ITS VALUES IN THE MASSIF OF SHARR MOUNTAIN - MACEDONIA a phase which coincides with different phases of vegetation. This study has been done for the first time especially within the Macedonian Flora, a study which completes the research of the Sharr Mountain Flora. The study is concentrated in 9 stations in the Sharr Mountains. The accumulation of the scientific material was conducted from early spring until late autumn, preparing herbarium, accompanied by data for site-collection, date, biotope etc. During this study a rich material has been collected, of about 300 exemplars. From the previous floristic analysis so far, it results that the Flora of the Sharr Mountain is rich with different types. The selected material consists of 72 families, 221 genders and around 552 types (see species table nr. 2).